Varicocoelectomy in adolescents: Laparoscopic versus open high ligation technique - Moreira-Pinto João; Osório Angélica; Carvalho Fátima; de Castro João Luís; de Sousa José Ferreira; Enes Carlos; Reis Armando; Cidade-Rodrigues José Alfredo (Wolters Kluwer Medknow Publications, 2011)
Background: Treatment of varicocoele is aimed at eliminating the retrograde reflux of venous blood through the internal spermatic veins. The purpose of this investigation was to compare laparoscopic varicocoelectomy (LV) with open high ligation technique in the adolescent population. Materials and Methods: We retrospectively evaluated 33 adolescents who underwent varicocoelectomy at our paediatric hospital, between May 2004 and September 2008. Patients were divided into two groups depending on the technique: those who had an LV and those submitted to an open varicocoelectomy (OV). We analysed side, age of surgery, follow-up period and the incidence of recurrence/persistence, hydrocoele formation and wound complication. Results: There were 24 patients in the LV group and 9 in the OV group. All varicocoeles were in the left side. Mean age was 12 years in both groups. Mean follow-up time was 32 months for the LV group and 38 months for the OV group (P = 0.49). There was no significant difference in the incidence of hydrocoele in both the groups (25% versus 22%, P = 0.626). There was no recurrence/persistence on the LV group, while in the OV group there were three cases (P = 0.015). Conclusion: LV seems more efficient than open high ligation technique in the treatment of adolescents′ varicocoeles. Larger series are necessary to draw more reliable conclusions.